Answer:
Explanation:
y=-x+2 equation 1
y=3x-2 equation 2
sub equation 1 into 2
-x+2=3x-2
-x+2-3x+2 =0 (bring everything to one side and to equal 0)
-4x+4=0 (collect like terms and go with the sign given)
-4x=-4 (bring 4 over to the other side to isolate)
-4x/-4=-4/-4 (divide to isolate)
x=1
y=-3x+3 equation 1
2x+y=1 equation 2
y=-2x-1 Rearrage equation 2 (now equation 3)
sub equation 1 into 3
-3x+3=-2x-1
-3x+3+2x+1 =0 (bring everything to one side and to equal 0)
-x+4=0 (collect like terms and go with the sign given)
-x=-4 (bring 4 over to the other side to isolate)